Solve for z 3(2z+1)-7=23

Math
3(2z+1)-7=23
Simplify 3(2z+1)-7.
Tap for more steps…
Simplify each term.
Tap for more steps…
Apply the distributive property.
3(2z)+3⋅1-7=23
Multiply 2 by 3.
6z+3⋅1-7=23
Multiply 3 by 1.
6z+3-7=23
6z+3-7=23
Subtract 7 from 3.
6z-4=23
6z-4=23
Move all terms not containing z to the right side of the equation.
Tap for more steps…
Add 4 to both sides of the equation.
6z=23+4
Add 23 and 4.
6z=27
6z=27
Divide each term by 6 and simplify.
Tap for more steps…
Divide each term in 6z=27 by 6.
6z6=276
Cancel the common factor of 6.
Tap for more steps…
Cancel the common factor.
6z6=276
Divide z by 1.
z=276
z=276
Cancel the common factor of 27 and 6.
Tap for more steps…
Factor 3 out of 27.
z=3(9)6
Cancel the common factors.
Tap for more steps…
Factor 3 out of 6.
z=3⋅93⋅2
Cancel the common factor.
z=3⋅93⋅2
Rewrite the expression.
z=92
z=92
z=92
z=92
The result can be shown in multiple forms.
Exact Form:
z=92
Decimal Form:
z=4.5
Mixed Number Form:
z=412
Solve for z 3(2z+1)-7=23

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top